The Effect of Nutrition Counseling on the Level of Knowledge and Compliance of Hypertension Diet in Inpatients at Sibuhuan General Hospital, Padang Lawas Regency - Manurung, Jelita; Winda Rizki Pebrina Batubara; Siti Aisyah; Monika Helen Sinaga; Fikriyah Arfina Nainggolan (JURNAL KESMAS DAN GIZI (JKG), 2025)
Failure to adhere to the prescribed diet can contribute to a rise in hypertension cases. A key preventive measure for hypertension is maintaining a balanced diet, which necessitates sufficient knowledge about nutrition, particularly in relation to hypertension. The degree of compliance with the recommended diet significantly influences the occurrence of hypertension. Therefore, the objective of this study was to assess the impact of nutritional counseling on the knowledge and adherence to the hypertension diet among hospitalized patients at Sibuhuan General Hospital in Padang Lawas Regency. This research utilized a Quasi-Experimental design with a one-group pre-test and post-test approach. The study's population consisted of 80 hypertensive patients admitted to Sibuhuan General Hospital. A sample of 36 individuals was selected based on specific inclusion and exclusion criteria, and data were collected using questionnaires. The findings revealed a notable effect of nutritional counseling on improving both knowledge and dietary adherence, with a significance value of 0.000 (p-value = 0.000 < 0.05). In conclusion, nutritional counseling effectively enhances both knowledge and compliance with the hypertension diet among patients. It is strongly recommended that healthcare providers take more initiative in spreading information about hypertension.